The psychology of wealth understand your relationship with money and achieve prosperity - Richards, Charles L. (New York McGraw-Hill, 2012)
In this fascinating exploration of the delicate relationship between money and the human mind, clinical psychologist Richards explains that discovering our sense of self is the key to determining our relationship with money. He contends that credit or debt can be useful tools for building personal growth--"if applied properly."
How do we define wealth? -- The evolution of wealth -- Finding your dream -- Self-esteem and its influence on wealth -- The stream vs. the rock -- Value is what you get -- Redefining your perspectives -- Cycles of giving back -- I'm going through a phase -- Painting a new portrait of prosperity -- Knowing where to plant your feet -- Conclusion: the whole elephant.
Includes bibliographical references and index.
Keywords: Money -- Psychological aspects; Wealth -- Psychological aspects